Phenotypic plasticity and genetic stock identification of Sperata seenghala (Sykes, 1839), the giant river-catfish, at indus river, Sindh, Pakistan (Zoo Botanica, 2025)
Traditional fish identification is based on morphological characteristics, whereas DNA-based identification has recently been considered a more reliable alternative method. The catfish are a significant group of freshwater fishes. Sperata seenghala is among the largest freshwater catfish of the subcontinent, occurring in the Indus River. A morphometric study concluded that the indus river system Sperata is closely related to S. seenghala with some physical differences. However, in the literature on Pakistan's fish diversity, only S. seenghala is documented. Research on Speratra in the Jamshoro stretch of the indus river revealed it as S. seenghala. This ambiguity in the nomenclature of S. seenghala needs genetic identification to resolve this issue. Thus, the present study evaluated the phenotypic plasticity and genetic stock identification of the S. seenghala at the Indus River, Sindh, Pakistan.There were 151 fish specimens collected from the commercial fish catch at the indus river, Jamshoro, from August 2020 to July 2022. The fish were measured for total length (TL) (cm) and body weight (g) on the spot and then brought to the laboratory for morphological identification and genetic study. The PCR (polymerase chain reaction) was used to amplify the mitochondrial COI gene using a primer pair for Fish F1 and Fish R1 primers. The sequencing, genetic variation, and phylogenetic relationships were established using DNAMAN and MEGA version 7 software. The study concluded that morphologically and genetically Sperata species occurring in the indus river is S. seenghala, and there was no evidence of phenotypic plasticity or genetic difference.  The present study aims to identify genetically S. seenghala of the indus river in Pakistan.
Keywords: Catfish; Sperata seenghala; morphology; genetic study; indus river